2020
DOI: 10.5539/ijbm.v15n9p93
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Centers Ambience-Customer Behavioral Intentions Relationship: The Mediating Role of Customer Emotional States

Abstract: This research paper aims to investigate how the ambient conditions in fitness centers affect customer behavioral intentions through examining the mediating role of customer emotional states while in the fitness center.  To this end, a conceptual model of relevant research variables was developed based on the extant literature. A questionnaire survey was administered to a convenient sample of 420 fitness center members approached in 10 randomly selected fitness centers in Jordan. The model was validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Brand image refers to the perception that consumers have of a brand, while consumer buying intentions refer to the likelihood that a consumer will purchase a product or service. Research has shown that brand image can have a significant impact on consumer buying intentions (Jiang et al, 2023;Nusairat et al, 2021). For example, a positive brand image can increase consumer trust and loyalty, which can lead to higher buying intentions.…”
Section: Literature Review and Hypothesis Development A Brand Image A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Brand image refers to the perception that consumers have of a brand, while consumer buying intentions refer to the likelihood that a consumer will purchase a product or service. Research has shown that brand image can have a significant impact on consumer buying intentions (Jiang et al, 2023;Nusairat et al, 2021). For example, a positive brand image can increase consumer trust and loyalty, which can lead to higher buying intentions.…”
Section: Literature Review and Hypothesis Development A Brand Image A...mentioning
confidence: 99%
“…On the other hand, a negative brand image can decrease consumer trust and loyalty, which can lead to lower buying intentions. Additionally, factors such as user-generated content, social media marketing, celebrity endorsement, and product aesthetics can also influence consumer buying intentions through their impact on brand image (Firmanza & Artanti, 2022;Jia et al, 2022;Jiang et al, 2023;Nusairat et al, 2021)…”
Section: Literature Review and Hypothesis Development A Brand Image A...mentioning
confidence: 99%
“…Using various social media (e.g., Facebook, Youtube, Instagram, Twitter, etc. ), people can share their experiences and satisfaction (Nusairat et al, 2021;Roma & Aloini, 2019). Even nowadays, firms offer financial benefits to professional content creators for creating such UGCs (Mayrhofer et al, 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Past studies have indeed highlighted the significance of management and data analysis in mitigating processes and creativity of innovation (Olszak and Kisielnicki 2016 ; Perry-Smith and Mannucci 2017 ; Bresciani et al 2018 ). In this regard, countless of data points need to be expounded to create new products, processes or business models, and new ways to approach consumers need to be identified, to increase customer satisfaction (Al-Okaily et al 2022c ; Shipilov et al 2017 ; Markides and Anderson 2006 ; Mahmoud et al 2018 ; Hammouri et al 2021 ; Nusairat et al 2021 ). Indeed, big data analytics can facilitate consumer behavior analysis (Levine et al 2017 ; Hofacker et al 2016 ; Peteraf et al 2013 ; Kannan and Li 2017 ), while predictive analytics could help in understanding the behavior of users and consumers (Markides and Anderson 2006 ; Lu and Weng 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%